Sustained Anti-VEGF Delivery via Hydrogel Implant Achieves Non-Inferior Visual and Anatomical Outcomes in Neovascular AMD: A 24-Month Randomized Controlled Trial - Habiburrahman Said; Oliva Azalia Putri; Linda Purnama (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2025)
Introduction: Neovascular age-related macular degeneration (nAMD) requires frequent anti-VEGF intravitreal injections, creating substantial treatment burden. This study compared the 24-month efficacy and safety of a sustained-release anti-VEGF hydrogel implant versus monthly ranibizumab in treatment-naive nAMD eyes. Methods: This prospective randomized controlled trial enrolled 126 eyes (96 patients; 30 bilateral) with treatment-naive nAMD at a private hospital in Palembang, Indonesia (January 2022–December 2024). Eyes were randomized 1:1 to a biodegradable anti-VEGF hydrogel implant (n=64) or monthly ranibizumab 0.5 mg (n=62). The primary outcome was non-inferiority of the mean best-corrected visual acuity (BCVA) change (LogMAR) at 24 months (margin: 0.10 LogMAR). Analyses used linear mixed-effects models with generalized estimating equations to account for inter-eye correlation. Results: Mean BCVA improved by −0.24±0.18 LogMAR (≈12 letters) in the hydrogel group and −0.22±0.20 LogMAR (≈11 letters) in the ranibizumab group (difference: −0.02; 95% CI: −0.09 to 0.05; p=0.578; non-inferiority confirmed). The hydrogel group required 77.8% fewer injections (4.8±1.2 vs 21.6±3.4; p<0.001). Safety profiles were comparable. Conclusion: The sustained-release anti-VEGF hydrogel implant achieved non-inferior visual and anatomical outcomes versus monthly ranibizumab while reducing injection burden by 77.8% over 24 months. Multicenter validation is warranted.